Life-threatening complications and mortality of minimally invasive pectus surgery - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2018)
The prevalence and type of life-threatening complications related to the minimally invasive repair of pectus excavatum (MIRPE) and bar removal are unknown and underreported. The purpose of this communication is to make surgeons aware of the risk of these life threatening complications as well as the modifications which have been developed to prevent them. Methods: Data related to life-threatening complications of Pectus Excavatum (PE) patients was obtained from four sources: 1. A survey of Chest Wall International Group (CWIG) surgeons who specialize in repairing congenital chest wall malformations, 2. Papers and case reports presented at CWIG meetings, 3. Review of medico-legal cases from the USA and 4. A systematic review of the literature related to major complications post MIRPE. Results: From 1998 to 2016, we identified 27 published cases and 32 unreported life-threatening complications including: cardiac perforation, hemothorax, major vessel injury, lung injury, liver injury, gastrointestinal problems, and diaphragm injury. There were seven cases of major complications with bar removal (reported and non-reported) with two lethal outcomes. Mortality data with bar placement surgery: Four published death cases and seven unpublished death cases. The overall incidence of minor & major complications post MIRPE has been reported in the literature to be 2-20%. The true incidence of life-threatening complications and mortality is not known as we do not know the overall number of procedures performed world wide. However, based on data extrapolated from survey information, the pectus bar manufacturer in the USA, literature reports, and data presented at CWIG meetings as to the number of cases performed we estimated that approximately fifty thousand cases have been performed and that the incidence of life-threatening complications is less than 0.1% with many occurring during the learning curve. Analysis of the cases identified in our survey revealed that previous chest surgery, pectus severity and inexperience were noted to be significant risk factors for mortality. Conclusions: Published reports support the safety and efficacy of MIRPE; however major adverse outcomes are underreported. Although major complications with MIRPE and pectus bar removal surgery are very rare, awareness of the risk and mortality of life-threatening complications is essential to ensure optimal safety. Factors such as operative technique, patient age, pectus severity and asymmetry, previous chest surgery, and the surgeon's experience play a role in the overall incidence of such events. These preventable events can be avoided with proper training, mentoring, and the use of sternal elevation techniques. Type of study: Treatment Study. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Pectus excavatum; Mortality; Morbidity; Life-threatening complications; Minimally invasive repair; Nuss procedure; MIRPE; Cardiac injury; Pectus bar removal; Chest Wall deformity; NUSS-PROCEDURE; EXCAVATUM REPAIR; BAR REMOVAL; CARDIAC INJURY; HEMORRHAGE; EROSION; DISPLACEMENT; OBSTRUCTION; PERFORATION; EXPERIENCE